Laparoscopic Versus Open Partial Nephrectomy for Stage T1a of Renal Tumors - Rezaeetalab, Gholam Hossein; Karami, Hormoz; Dadkhah, Farid; Simforoosh, Nasser; Shakhssalim, Nasser (Urology Journal, 2016)
Purpose: Partial nephrectomy is the gold standard treatment for small kidney masses. Data on the comparison oflaparoscopic (LPN) versus open partial nephrectomy (OPN) are based on retrospective studies. Thus, we plannedto compare these two techniques in a prospective trial. Materials and Methods: The study population consisted of patients over 18 years old with single renal mass of≤ 4 cm. Patients were divided into two groups considering their preference. Study arms were matched accordingto age, gender, tumor size and location and renal nephrometry score. Mean operation time, warm ischemia time,hospital stay, peri-operative complications and changes in glomerular filtration rate (GFR) after 1 month were recordedand compared in two groups. Patients’ satisfaction score, visual analogue scale and narcotics use to controlpost-operative pain were also studied. Results: 34 and 31 patients underwent LPN and OPN, respectively. There was no significant difference betweenOPN and LPN regarding hospital stay (4.1 versus 4.6 days; P = .37), mean hemoglobin drop (2.17 and 1.96 g/dL;P = .62), changes in GFR and positive margin (1 versus 3 p=.40). LPN was accompanied with longer mean surgerytime (180 min versus 127 minutes; P < .001) and higher rate of urologic complications (P = .04); nevertheless,patient satisfaction rate was higher (P = .02) and dose of narcotics necessary for controlling post-operative painwas lower (P = .04) in LPN. Conclusion: This clinical trial shows that LPN has some benefits over OPN, including decreased post-operativepain and higher patient satisfaction. However, extra caution should be considered in the issue of tumor margin andurinary leakage in LPN.